(untitled) (Homoeopathy for All, 2022)
Tissue Salts are present in extremely small quantities in every cell of the human body. Some salts are also found in the intercellular fluids, which nourish the cells and act as a messaging medium for the nervous system. A proper balance of salts within the intercellular fluid allows for efficient messaging traffic between the cells and organs. Mineral salts also assist in the elimination of older, damaged cells and cellular waste products. Mineral salts coat the organs of the body, provide nourishment to the elastic fibers and are essential components of bones, teeth and connective tissues. Without them, nerve cells would fail to form. Cell salts are in ionic form and very digestible. By putting the substance under the tongue it bypasses the digestive juices and goes directly in the bloodstream in this ionic form. The cells recognize this form as useable and immediately suck it into the cellular membrane. Once enough of the substance has been accepted and the body is balanced an intake of more cellular salt will do us no harm and be excreted from the system. This is not like herb, drug or nutritional supplement where the body has to expend energy to get rid of the excess.